Symbolic Communication in Post-Dayton Bosnia and Herzegovina - Rekść, Magdalena (Specialized Languages in Intercultural Communication, 2020)
Bosnia and Herzegovina is widely considered a dysfunctional state where political institutions do not work. The Dayton agreement has shaped a bizarre system of government in which ethnicity remains the most important value. Such a situation is very dangerous in a multi-ethnic country, considering difficult historical past and the lack of implementation of transitional justice. The three constituent nations of Bosnia and Herzegovina do not live together, but side by side, many speak about ghettoization of the country. This text focuses on the symbolic communication in Bosnia or more precisely, its lack. Although Serbs, Croats and Bosniaks speak very similar languages, they do not understand each other on a symbolic level. Each of them has a different vision of the past, present and future and the heroes become enemies in the discourses of neighbours. It should not come as a surprise that that there is no shared symbolic capital in Bosnia and Herzegovina, but without it a collective identity cannot be created and implemented. There are individuals and circles that try to create common Bosnian identity, but their range and capability are very limited, since the principle of ethnicity and ethnic nationalism plays the most important role. Unfortunately, such a situation confirms the pessimistic forecasts regarding the future of the country.